Quality cost analysis and a firm application - Çevik, Zülküf (My University, 2011)
Son yıllarda ulusal ve uluslar arası pazarlarda rekabet artmış durumdadır. Birçok firma bu pazarlarda faaliyetlerine devam edebilmek için üretim maliyetlerini düşürmeye, ürün kalitesini ise yükseltmeye çalışmaktadır. Bu sebeple kalite maliyetlerinin önemi ülkemizde her geçen gün artmaktadır. Bu çalışmada bir işletme için kalite maliyet sisteminin önemini vurgulamak ve kalite maliyet analizi yapmak amaçlanmıştır. Bu bağlamda da kalite maliyetlerinin firmaların toplam üretim maliyetleri üzerindeki etkisi incelenmiştir. Bu çalışma oluşturulurken literatür taraması ve teorik araştırma yapılmıştır. Yapılan bu araştırma sonucunda bir firma uygulaması yapılmıştır. Bu uygulamada kalite maliyetleri raporlanması vurgulanmıştır. Ülkemizdeki firmaların ulusal ve uluslar arası pazarlarda faaliyet gösterebilmeleri için kalite maliyet sistemlerine daha fazla önem vermeleri gerekir. Kalite maliyet sistemi karlılığı arttırır, maliyetleri düşürür ve buna ek olarak üretim verimliliğini arttırır. Bu nedenle kalite maliyet sistemi, sistemin uygulanabileceği her işletmede kurulmalıdır.

Currently, the competition in the national and international markets has considerably heated up. Many companies try to decrease their production costs and increase its product quality in order to survive in the fierce market conditions. In this respect, quality costs are gaining ever growing importance in our country. In this study, the quality cost analysis has been studied in order to show the significance of quality cost systems for a company. The study also aims to demonstrate the effects of quality costs on the total costs of a firm. The research methodology of this study is literature review and theoretical search on the quality costs system. According to this review and theoretical search, a firm application has been performed. By making this application, the reporting of quality costs has been emphasised. Companies in Turkey should pay more importance to quality cost systems, in order to survive in the market. The quality cost system increases profitability and reduces certain costs, and in addition, utilizes production efficiency. Therefore, the quality cost system should be established in every company in which it can be applicable.
Keywords: Kalite Maliyetleri; Maliyet Analizi; Maliyet Muhasebesi; Muhasebe